SAT0247 FEMALE SEX AND AGE AT DIAGNOSIS ARE ASSOCIATED WITH A DECREASED POSSIBILITY OF DRUG DISCONTINUATION IN GIANT CELL ARTERITIS: DATA FROM A MULTICENTER PROSPECTIVE COHORT OF 177 PATIENTS. (June 2019) - Christina, Tsalapaki; Lazarini, Argyro; Tektonidou, Maria; Sfikakis, Petros; Dania, Vasiliki; Boki, Kyriaki; Kaltsonoudis, Evripidis; Voulgari, Paraskevi V.; Evangelatos, Gerasimos; Iliopoulos, Alexios; Theotikos, Evangelos; Elezoglou, Antonia; et al.
Abstract : Background: Giant cell arteritis (GCA) usually requires long-term therapy with corticosteroids and/or Disease Modifying Anti-rheumatic Drugs (DMARDs) but the exact factors that are associated with drug discontinuation in these patients have not been well defined. Objectives: To evaluate the baseline or on-treatment factors that influence drug survival in GCA. Methods: Data were derived from an ongoing, multicenter, prospective cohort study of patients with GCA. During the 1st phase of the study, data regarding demographic and clinical characteristics at baseline, type of treatment, adverse events of therapy and co-morbidities were retrospectively collected and analyzed. Predictors of drug discontinuation were examined by univariate and multivariate logistic regression analyses. Results: One hundred and seventy seven patients were included in the study; 70% (n=120) were women with a mean age at diagnosis of 74 ± 8.4 years. Diagnosis was established by temporal artery biopsy in 127 patients (72%), ultrasound of temporal arteries in 37 patients (21%) and large vessel imaging in 10 patients (6%). At diagnosis, the median ESR and CPR were 103 mm/h and 63 mg/L, respectively. All patients were treated initially with pos corticosteroids (median daily starting dose: 41 mg), while 12 (7%) of patients received pulse steroids. At the 1st patient evaluation (median follow-up from diagnosis: 3 years), the median daily steroid dose was 5 mg, while in 34% (n= 62) and 8% (n= 14) of patients a synthetic or biologic DMARD had been added, respectively. During that period, 24% (n=43) of patients had discontinued corticosteroids and 18% (n=32) all treatments. By univariate analysis, DMARD use was associated with a higher possibility for corticosteroid discontinuation (OR=2.3, p=0.017) but by multivariate logistic regression analysis only female sex (OR=0.49, p=0.07) and age at diagnosis (OR=0.94, p=0.01) were associated with a decreased risk for corticosteroid discontinuation. Similar results were found for discontinuation of all drugs [female sex (OR=0.4, p=0.05) and age at diagnosis (OR=0.9, p=0.046)]. Conclusion: In this large GCA cohort, only one out of four patients managed to discontinue corticosteroids and 20% all treatments ∼3 years after diagnosis. Multivariate analysis revealed only female sex and age at diagnosis as independent factors for treatment discontinuation. Acknowledgement: Supported by grants from the Greek Rheumatology Society and Professional Association of Rheumatologists. Disclosure of Interests: None declared